Social Behavior, Community Composition, Pathogen Strain, and Host Symbionts Influence Fungal Disease Dynamics in Salamanders - Cowgill, Mae; Zink, Andrew G.; Sparagon, Wesley; Yap, Tiffany A.; Sulaeman, Hasan; Koo, Michelle S.; Vredenburg, Vance T. (Frontiers in Veterinary Science, 2021)
The emerging fungal pathogen, Batrachochytrium dendrobatidis (Bd), which can cause a fatal disease called chytridiomycosis, is implicated in the collapse of hundreds of host amphibian species. We describe chytridiomycosis dynamics in two co-occurring terrestrial salamander species, the Santa Lucia Mountains slender salamander, Batrachoseps luciae, and the arboreal salamander, Aneides lugubris. We (1) conduct a retrospective Bd-infection survey of specimens collected over the last century, (2) estimate present-day Bd infections in wild populations, (3) use generalized linear models (GLM) to identify biotic and abiotic correlates of infection risk, (4) investigate susceptibility of hosts exposed to Bd in laboratory trials, and (5) examine the ability of host skin bacteria to inhibit Bd in culture. Our historical survey of 2,866 specimens revealed that for most of the early 20th century (approximately 1920-1969), Bd was not detected in either species. By the 1990s the proportion of infected specimens was 29% and 17% (B. luciae and A. lugubris, respectively), and in the 2010s it was 10% and 17%. This was similar to the number of infected samples from contemporary populations (2014-2015) at 10% and 18%. We found that both hosts experience signs of chytridiomycosis and suffered high Bd-caused mortality (88% and 71% for B. luciae and A. lugubris, respectively). Our GLM revealed that Bd-infection probability was positively correlated with intraspecific group size and proximity to heterospecifics but not to abiotic factors such as precipitation, minimum temperature, maximum temperature, mean temperature, and elevation, or to the size of the hosts. Finally, we found that both host species contain symbiotic skin-bacteria that inhibit growth of Bd in laboratory trials. Our results provide new evidence consistent with other studies showing a relatively recent Bd invasion of amphibian host populations in western North America and suggest that the spread of the pathogen may be enabled both through conspecific and heterospecific host interactions. Our results suggest that wildlife disease studies should assess host-pathogen dynamics that consider the interactions and effects of multiple hosts, as well as the historical context of pathogen invasion, establishment, and epizootic to enzootic transitions to better understand and predict disease dynamics.